The Treatment and Prognosis of Refractory and Super-Refractory Status Epilepticus - Gollwitzer, Stephanie; Hamer, Hajo M. (Neurology International Open, 2017)
Refractory status epilepticus (RSE) is defined as status epilepticus (SE) persisting over 60 min and resistant to treatment with benzodiazepines and non-sedating antiepileptic drugs. The term super-refractory status epilepticus (SRSE) refers to a refractory episode continuing under general anesthesia for more than 24 h. RSE is treated with a combination of non-sedating AED and i. v. anesthetics; first choice drugs are midazolam, propofol and thiopental. The management of super-refractory status epilepticus (SRSE) is challenging as clear evidence-based guidelines are lacking. Recommendations are mainly based on case reports and small case series. Therapeutic options include ketamine, inhalational anesthetics, steroids and immunoglobulins. Ketogenic diet, electroconvulsive therapy and epilepsy surgery are also considered as potentially effective. A promising new approach is the neurosteroid allopregnanolone. Mortality of RSE and SRSE is largely influenced by the etiology and is markedly higher as compared to non-refractory status epilepticus. It was reported to be about 30% and 50%, respectively.
Keywords: status epilepticus; refractory status epilepticus; superrefractory status epilepticus